New directions in cognitive linguistics. - Evans, Vyvyan; Pourcel, Stephanie (Human cognitive processing, 2009)
Nearly three decades since the publication of the seminal Metaphors We Live By, Cognitive Linguistics is now a mature theoretical and empirical enterprise, with a voluminous associated literature. It is arguably the most rapidly expanding ‘school’ in modern linguistics, and one of the most exciting areas of research within the interdisciplinary project known as cognitive science. As such, Cognitive Linguistics is increasingly attracting a broad readership both within linguistics as well as from neighbouring disciplines including other cognitive and social sciences, and from disciplines within the humanities. This volume contains over 20 papers by leading experts in cognitive linguistics which survey the state of the art and new directions in cognitive linguistics. The volume is divided into 5 sections covering all the traditional areas of study in cognitive linguistics, as well as newer areas, including applications and extensions. Sections include: Approaches to semantics; Approaches to metaphor and blending; Approaches to grammar; Language, embodiment and cognition; Extensions and applications of cognitive linguistics.